Corporate governance myths: Comments on Armstrong, Guay, and Weber - Brickley, James A.; Zimmerman, Jerold L. (Journal of Accounting and Economics, 2010)
This paper argues that academics, politicians, and the media have six commonly held but misguided beliefs about corporate governance. While Armstrong et al. (2010) discuss some of these misconceptions, a wider recognition that these beliefs are actually “myths” is important. They include: (1) a common definition of “corporate governance” exists; (2) a useful distinction is “internal” versus “external” governance mechanisms; (3) outside directors perform two separable roles: to advise and monitor managers; (4) research has identified “good” and “bad” governance practices; (5) a “good” governance index can be constructed; and (6) corporate governance “best practices” can be deduced from peer data.